Analysing direct air capture for enabling negative emissions in Germany: an assessment of the resource requirements and costs of a potential rollout in 2045 - Block, Simon; Viebahn, Peter; Jungbluth, Christian (Frontiers in Climate, 2024)
Direct air capture (DAC) combined with subsequent storage (DACCS) is discussed as one promising carbon dioxide removal option. The aim of this paper is to analyse and comparatively classify the resource consumption (land use, renewable energy and water) and costs of possible DAC implementation pathways for Germany. The paths are based on a selected, existing climate neutrality scenario that requires the removal of 20 Mt of carbon dioxide (CO2) per year by DACCS from 2045. The analysis focuses on the so-called "low-temperature" DAC process, which might be more advantageous for Germany than the "high-temperature" one. In four case studies, we examine potential sites in northern, central and southern Germany, thereby using the most suitable renewable energies for electricity and heat generation. We show that the deployment of DAC results in largescale land use and high energy needs. The land use in the range of 167 to 353 km 2 results mainly from the area required for renewable energy generation. The total electrical energy demand of 14.4 TWh per year, of which 46% is needed to operate heat pumps to supply the heat demand of the DAC process, corresponds to around 1.4% of Germany's envisaged electricity demand in 2045. 20 Mt of water are provided yearly, corresponding to 40% of the city of Cologne`s water demand (1.1 million inhabitants). The capture of CO2 (DAC) incurs levelised costs of 125 to 138 EUR per tonne of CO2, whereby the provision of the required energy via photovoltaics in southern Germany represents the lowest value of the four case studies. This does not include the costs associated with balancing its volatility. Taking into account transporting the CO2 via pipeline to the port of Wilhelmshaven, followed by transporting and sequestering the CO2 in geological storage sites in the Norwegian North Sea (DACCS), the levelised costs increase to 161 to 176 EUR/tCO2. Due to the longer transport distances from southern and central Germany, a northern German site using wind turbines would be the most favourable.